Modeling and Simulation of Machining-Induced Surface Integrity Characteristics of NiTi Alloy - KAYNAK, YUSUF (ELSEVIER SCIENCE BV, 2015)
NiTi shape memory alloys have gained increased interest in various industries, including biomedical and aerospace applications due to their unique properties such as shape memory effect and superelasticity. Martensitic phase transformation in NiTi significantly affects the surface integrity characteristics. This phase transformation needs to be better understood to control and enhance the shape memory and microstructural properties of NiTi shape memory alloys. This study presents results of combined experimentation and simulation of cutting-induced phase transformation in orthogonal machining of NiTi shape memory alloys. A phenomenological modeling approach was utilized to model machining-induced phase transformation. NiTi shape memory alloys alloy were in austenite phases at room temperature. The transformation during dry machining process from austenite to martensite phases, and the resulting volume fraction was successfully simulated using DEFORM 2-D software by implementing a user-defined subroutine. The developed model is capable of capturing the trend of variations in volume fracture and the depth of transformed layer as a function of cutting speed. (C) 2015 The Authors. Published by Elsevier B.V.
Keywords: Machining; Surface integrity; Finite element method; Phase transformation; NiTi Alloy; SHAPE-MEMORY; CORROSION-RESISTANCE; TOOL-WEAR; MICROSTRUCTURE; BEHAVIOR; WORK